2023
DOI: 10.1101/2023.01.19.524726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Minimal impact of proprioceptive loss on implicit sensorimotor adaptation and perceived movement outcome

Abstract: Our ability to produce successful goal-directed actions involves multiple learning processes. Among these, implicit adaptation is of utmost importance, keeping our sensorimotor system well-calibrated in response to changes in the body and environment. Implicit adaptation is assumed to be driven by a sensory prediction error, the difference between the predicted and actual sensory consequences of a movement. Whereas most models of implicit adaptation have focused on how visual information defines the sensory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Thus, we predicted that participants would exhibit implicit adaptation during the isometric aiming task by slowly drifting the direction of their force exertion away from the target when exposed to clamped visual feedback. Further, we also predicted that adaptation would reach similar asymptotic levels compared to those found in previous clamped visual feedback reaching studies (e.g., Kim et al, 2018;Morehead et al, 2017;Tsay et al, 2023), based on the notion that the efferent sensory component would compensate for the missing afferent contributions.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, we predicted that participants would exhibit implicit adaptation during the isometric aiming task by slowly drifting the direction of their force exertion away from the target when exposed to clamped visual feedback. Further, we also predicted that adaptation would reach similar asymptotic levels compared to those found in previous clamped visual feedback reaching studies (e.g., Kim et al, 2018;Morehead et al, 2017;Tsay et al, 2023), based on the notion that the efferent sensory component would compensate for the missing afferent contributions.…”
Section: Introductionsupporting
confidence: 58%
“…However, in a recent study examining implicit adaptation during target-directed reaching movements in rare individuals with deafferentation (severe, or complete, proprioceptive loss), Tsay et al (2023) found similar adaptation between deafferented individuals and healthy controls. Previous studies utilizing visuomotor rotations or forcefield perturbations have also shown comparable levels of adaptation between individuals with deafferentation and healthy control participants (Bernier et al, 2006;Sarlegna et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…The importance of perceptual error was first implied in the PReMo model ( Tsay et al, 2022b ), which also proposed that a misperceived hand location is the driving signal for implicit adaptation. However, this previous work improperly called this perceptual error a proprioceptive error, leading to the impression that it is a type of sensory error (but see their new unpublished Tsay et al, 2024 ). The two models differ fundamentally in their conceptualization of how different cues contribute to the error signal.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of perceptual error was first implied in the PReMo model (Tsay, Kim, Haith, et al, 2022), which also proposed that a misperceived hand location is the driving signal for implicit adaptation. However, this previous work improperly called this perceptual error a proprioceptive error, leading to the impression that it is a type of sensory error (but see their new unpublished Tsay et al, 2024). The two models differ fundamentally in their conceptualization of how different cues contribute to the error signal.…”
Section: Discussionmentioning
confidence: 99%